Knockdown of RFC4 inhibits cell proliferation of oral squamous cell carcinoma in vitro and in vivo - Pengyue You; Di Wang; Zheng Liu; Shuzhen Guan; Ning Xiao; Haotian Chen; Xin Zhang; Lichuan Wu; Guizhen Wang; Haitao Dong (FEBS Open Bio)
Oral squamous cell carcinoma (OSCC) is the one of the most common types of malignant tumor found in the head and neck area. Replication factor C subunit 4 (RFC4), an oncogene active in various human cancers, has been rarely studied in OSCC. In the present study, bioinformatics analysis identified RFC4 as a potential key target in OSCC progression. Additional experiments showed that RFC4 expression was significantly higher in OSCC tumor tissues than in normal tissues. Knockdown of RFC4 led to G2/M phase cell cycle arrest and inhibited the proliferation of OSCC cells both in vitro and in vivo. High RFC4 expression in OSCC tumors was linked to increased levels of MET, along with reduced levels of CD274 and CD160. Overall, the present study reveals that RFC4 may play a pivotal role in OSCC tumorigenesis and could serve as a potential predictive marker for the efficacy of immunotherapy.